Risk perception of health problems among travelers visiting a travel clinic in Bangkok, Thailand - Thanyapat Hiranrusme; Watcharapong Piyaphanee; Jaranit Kaewkungwal; Udomsak Silachamroon; Wattana Leowattana; Lapakorn Chatapat; Wasin Matsee (Tropical Diseases, Travel Medicine and Vaccines, 2020)
Abstract Background Effective pre-travel consultations cannot be achieved only through individual risk assessment and advice on vaccinations and chemoprophylaxis. Travelers’ perceptions of the risk of health problems represent another key factor in successful risk communication and co-operation with pre-travel advice. The objective of this study was to determine perception of travel-related health risks among Thais and westerners visiting the Thai Travel Clinic for consultation before visiting developing countries. Methods A novel pictorial scale questionnaire-based study was conducted with both Thai and western travelers who visited the Thai Travel Clinic for pre-travel consultation. All participants were approached before and after completing the consultation, and were asked about their demographic data and perceptions of travel-related health risk. The perceptions of risk before and after consultation were compared using the McNemar test, and were also compared with the actual estimated risk. Results During May to November 2019, 594 travelers (330 Thais and 264 Westerners) were enrolled and completed the pictorial scale questionnaires. Most Thai travelers visited Africa/South America (63%), and 20% had previously received counseling. Westerners were mostly backpackers (37.5%), traveling for > 30 days (71.6%), while 43.6% had previously received counseling. Overall, the westerners (n = 264) changed their risk perceptions slightly after counseling in contrast with the Thais. The change in perception of most health problems was observed statistically significant (p-value < 0.05) after receiving pre-travel consultation among both groups of travelers. Risk perception among western travelers after consultation compared with estimated actual risk showed accurate risk perception toward most of health problems especially in travelers who had previously received counseling in ones’ home countries. Conclusions Risk perception of health problems plays an important role in successful risk communication and their response to pre-travel advices. Differences in risk perceptions were evident between the two groups. Therefore, this highlight the importance of obtaining pre-travel advice in one’s home country before travelling. Raised awareness of the risks should be emphasized during consultations for underestimated health risks, especially for rabid animal exposure and sexually transmitted diseases.